REVIEW OF ANOMALY DETECTION IN NETWORK USING MACHINE LEARNING APPROACH - Bhusari, Amit; Chaudhari, Prabhanjan; Bhusari, Dipali; Payghan, Amol (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In current era Real time networks using Information and Communication Technology (ICT) has a dominating impact on society, its economy and also security. More generally, ICT reinforce computers, mobile communication devices and networks. Widespread use of ICT is challenged by a group of people with malicious intent, whom we called as network intruders, cyber criminals, etc. Owing to these detrimental cyber attackers and cyber-crimes are of the international priorities and subject to trending research area. Anomaly detection is an important data analysis task which is useful for identifying the network intrusions. This paper is an attempt for reviewing the methods of an anomaly detection. The paper also discusses research challenges with the datasets used for network intrusion detection.